Teacher Strategies in Realizing Teacher Pedagogical Competence in High School - Annas Kuncoro Abdurrahman; Ruobing Ji (Indonesian Journal of Education Research (IJoER), 2023)
Purpose of the study: The aim of this research is to find out teacher strategies in realizing teacher pedagogical competence in high school. Methodology: This research is included in the type of descriptive qualitative research with a phenomenological approach. Data collection comes from interviews and observations. Interviews were conducted with six informants, consisting of two history subject teachers and two sociology subject teachers. The other informants were one class X student and one class XI student who still received instruction from the four teachers. Main Findings: The results of the research show: (1) The meaning of pedagogical competence for teachers in high school (2) Teacher strategies in realizing teacher pedagogical competence in high school are (a) the approach taken by teachers towards students, (b) teacher strategies are based on the approach taken by teachers towards students . Erving Goffman's dramaturgical theory provides an overview of the daily lives of individuals that occur on a stage. In the show there are two parts, namely the front stage which consists of setting, appearance and attitude. Novelty/Originality of this study: The research that is currently being carried out is updated with different approaches from the four high school teachers, resulting in different strategies. An approach can be likened to a map of the geographical conditions of an area, while a strategy is a plan for developing the potential of that area. So, to develop student potential, a teacher must be able to understand student needs in the teaching and learning process.